Hadith #666 - Sahih Muslim - Mu'adhah bint 'Abdullah معاذة بنت عبد الله (Sahih Muslim)
A woman asked ‘A’isha: Should one amongst us complete prayers abandoned during the period of menses? ‘A’isha said: Are you a Haruriya? When any one of us during the time of the Messenger of Allah (ﷺ) was in her menses (and abandoned prayer) she was not required to complete them.
Grade: Sahih

Hadith #668 - Sahih Muslim - Mu'adhah bint 'Abdullah معاذة بنت عبد الله (Sahih Muslim)
I asked ‘A’isha: What is the reason that a menstruating woman completes the fasts (that she abandons during her monthly course). but she does not complete the prayers? She (Hadrat ‘A’isha) said: Are you a Haruriya? I said: I am not a Haruriya, but I simply want to inquire. She said: We passed through this (period of menstruation), and we were ordered to complete the fasts, but were not ordered to complete the prayers.
Grade: Sahih